The promising roles of macrophages in geriatric hip fracture - Lu, Yi-ning; Wang, Ling; Zhang, Ying-ze (Frontiers in Cell and Developmental Biology, 2022)
As aging becomes a global burden, the incidence of hip fracture, which is fatal and the most common fracture in the elderly population, is rapidly increasing, and its extremely high lethality rate places significant medical and financial burdens on patients. Fractures trigger a complex set of immune responses, and recent studies have shown that with aging, the immune system declines or malfunctions in a process known as immune senescence, leading to disease and death; these phenomena are why elderly individuals typically exhibit chronically low levels of inflammation and increased rates of infection and chronic disease. Macrophages, which are key players in the inflammatory response, are critical in initiating the inflammatory response, clearing pathogens, controlling the innate and adaptive immune response and repairing damaged tissues.Tissue-resident macrophages(TRM) are widely present in tissues and perform immune sentinel and homeostatic functions. TRMs are not a homogeneous population, but are actually combinations of cells with similar functions and phenotypes. Immune system disorders caused by aging affect macrophages and thus the immune response after fracture in various ways. In this review, we outline current studies and discuss the potential link between monocytes and macrophages and their potential roles in hip fracture in elderly individuals.